FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN DAN ANALISIS KEBUTUHAN ORANGTUA YANG MENGALAMI KECEMASAN DENGAN BAYI SAKIT KRITIS DI NICU RSUD PROF.DR. MARGONO SOEKARDJO PURWOKERTO - Siwi, Adiratna Sekar; Fatimah, Sari; Emaliyawati, Etika (Universitas Muhammadiyah Magelang, 2017)
Baby with critical condition should receive care in NICU (Neonatal Intensive Care Unit). This process can trigger parents’ anxiety which can induce another problem such as difficulty to involve in decision making regarding patient’s condition. Parents’ anxiety can be caused by several factors depend on parents’ needs. This research aim to analyze factors that can influence parents’ anxiety during accompanied their baby in NICU and analyze their needs start from the least important until the most important. This research is a quantitative cross sectional study. Total respondent in this study are 70 persons with consecutive sampling method. All respondent in this study receive mother-baby questionnaire, HARS (Hamilton Anxiety Rating Scale) and NFNI (NICU Family Needs Inventory). Data analysis was conducted using Chi Square. From the result of the study we can get information that factor which related with parents’ anxiety is parents’ experience to taking care their baby in NICU (p value 0.000) and baby’s treatment length of stay (p value 0.000). And the parent’s needs during accompany their baby sorted from the most important one are need for closeness (65 % respondents), need for certainty (55 % respondents), need for comfort (30 % respondents), need for support (18.3 % respondents), and need for information (15 % respondents). Closeness between parents and baby during treatment, and parents’ experience to taking care their baby in NICU are very important because it can increase not only bonding between them but also baby’s condition. Parents’ involvement during delivering care to baby in NICU also can reduce patient’s length of treatment, increase quality of care, and reduce parents’ anxiety during accompanying their baby in NICU. Therefore further assessment for parents’ anxiety and needs during accompanying their baby in NICU is very crucial.